Bridging ESG and SDGs Clean Air and Water Through CSR Committee: A New Pathway for Sustainability in the Utility Sector - Supriyono, Supriyono; Fadly, Muhtad; Prasetyanto, Didik; Dwi Jayanti, Risca (Journal of Ecohumanism, 2024)
This study aims to bridge Environmental, Social, and Governance (ESG) principles with the Sustainable Development Goals (SDGs), particularly related to clean air and water, through the role of the Corporate Social Responsibility (CSR) committee in the utility sector. As global awareness of climate change rises, utility companies worldwide are adopting ESG strategies to reduce carbon emissions, improve energy efficiency, and manage water resources. This research proposes a new evaluation framework to assess the contribution of utility companies to achieving SDGs focused on air and water quality. Using data from annual reports and Refinitiv LSEG, the study examines the relationship between ESG scores, asset size, debt-to-equity ratio, and the moderating role of CSR committees in achieving SDG goals. Regression analysis results indicate that ESG scores have a significant positive influence on company contributions to achieving SDGs, especially in terms of clean air and water quality. Additionally, the CSR committee acts as an effective moderator in optimizing asset use and managing company debt to meet sustainability goals. This study provides both theoretical and practical contributions to support evidence-based decision-making for more sustainable policies in the utility sector.